A distributed admission control model for CoS networks using QoS and SLS monitoring - Lima, Solange (2003)
Achieving an admission control strategy for CoS networks covering both intra-domain and end-to-end operation is still an open issue. This paper discusses how AC can be carried out without adding significant complexity to the network control plane and proposes a distributed service-oriented AC model for these networks. The model only involves the network edge nodes leaving the network core unchanged. Ingress nodes perform implicit or explicit service-dependent AC based on both QoS and SLSs utilization metrics, obtained through on-line edge-to-edge monitoring performed at egress nodes. From an end-to-end perspective, the flow request is used both for AC and available service computation. Relevant aspects of the model interrelated areas and implementation key points are also discussed.